Pylorus resection in partial pancreaticoduodenectomy: impact on delayed gastric emptying - Hackert, Thilo; Hinz, Ulf; Hartwig, Werner; Strobel, Oliver; Fritz, Stefan; Schneider, Lutz; Werner, Jens; Büchler, Markus W. (The American journal of surgery, 2013)
Background - Partial pancreaticoduodenectomy (PD) is complicated by postoperative delayed gastric emptying (DGE) in up to 45% of patients. The aim of this study was to evaluate the impact of pylorus resection on DGE following PD. - Methods - Forty PD patients underwent pylorus resection with complete stomach preservation (prPD). They were compared with a pair-matched group of PD patients with pylorus preservation (ppPD) in a 1:1 ratio (age, sex, histopathology). The objectives were operative parameters, DGE incidence, morbidity, and length of hospital stay. - Results - DGE incidence was significantly lower after prPD (15.0% vs 42.5%; P = .0066). Operative parameters and surgical morbidity (other than DGE) were not different (27.5% prPD vs 30.0% ppPD). There was a trend toward a shorter hospital stay in the prPD group. - Conclusions - Resection of the pylorus with stomach preservation significantly reduces the frequency of DGE after PD without showing any disadvantage when compared with standard ppPD. This finding could be of high relevance for the clinical practice in routine PD and should consequently be investigated in a large randomized multicenter trial to create further evidence.